Exploring a Sense of Place and Nationalism in Sorayya Khan’s Five Queen’s Road - Parekh, Krupali; Kaushal, Urvashi (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
The paper explores minor communities living on the land of major ethnic groups, and analyses their predicament through the lens of sense of place and nationalism. A branch of human geography and environmental psychology has provided insight into the most fundamental aspect of attachment towards the place and - a bond between individual and nation or land. The novel Five Queen’s Road, by Sorayya Khan, opens the ground to study the connection between nationalism and place attachment. The central character- Dina Lal, refused to leave Lahore (Pakistan) after partition on account of his attachment to the place and the newly created nation in general. Even though he knew the fact that the partition was done on the basis of religious identity, i.e., India for Hindus and Pakistan for Muslims, and people were forced to migrate overnight, he refused to leave. Primarily, this paper provides an intersection between the 1947 partition, theories on the sense of place and nationalism, theories of sense of place, and nationalism. Additionally, it raises the question on the claim made by Pakistan authority who articulated an idealized view of Pakistan as a welcome place for religious minorities. It explores how Dina Lal’s family suffered because of his refusal to move from the place, which was becoming unsafe day by day. His attachment to place made him a victim of violence and later caused the disintegration of his family. The paper traces two essential aspects: the attachment with the place/nation and its consequences pertaining to the condition of minorities living in Pakistan after partition and their shattered hopes. It also deals with how a partition evokes the issue of belongingness, pain, violence, and traumatic memories.